Language profiles and literacy outcomes of children with resolving, emerging, or persisting language impairments - Snowling, MJ; Duff, FJ; Nash, HM; Hulme, C (Wiley, 2015)
Background Children with language impairment (LI) show heterogeneity in development. We tracked children from pre-school to middle childhood to characterize three developmental trajectories: resolving, persisting and emerging LI.